Integrasi Ilmu Agama dan Ilmu Umum dalam Perspektif Filsafat Islam: Studi di SMA Islam Nurul Musthofa - Mujiburrahman, Mujiburrahman; Rochayah, Anita (TSAQOFAH, 2026)
Islamic education, in principle, does not recognize a dichotomy between religious knowledge and general knowledge, as both are viewed as a unified body of knowledge originating from Allah SWT. However, in modern educational practice, separation between these two types of knowledge is still frequently observed, both in curriculum structures and in teaching–learning processes. This study aimed to examine the integration of religious and general knowledge in educational practice at SMA Islam Nurul Musthofa from the perspective of Islamic philosophy. The research employed a qualitative approach with a philosophical paradigm and a case study strategy, with data obtained through interviews with religious and general subject teachers, observations of learning processes, and document analysis of the school curriculum and policies. Data were analyzed thematically using an Islamic philosophical framework, particularly the concepts of knowledge integration, the relationship between ‘aql (intellect) and wahy (revelation), and Islamic thinkers’ views on the nature of knowledge. The findings show that the integration of religious and general knowledge at SMA Islam Nurul Musthofa is pursued through the inculcation of Islamic values in the learning process, the habituation of adab, and the strengthening of spiritual orientation in academic activities; religious knowledge functions as a value foundation, while general knowledge is positioned as a means to develop students’ intellectual abilities and skills. Nevertheless, this integration still requires reinforcement at the conceptual and methodological levels in order to become more systematic and consistent. This study affirms that the integration of knowledge from the standpoint of Islamic philosophy is a crucial foundation for realizing Islamic education that is holistic and oriented toward forming knowledgeable and well-mannered (berilmu and beradab) individuals.